Investigating the effects of education and labour market challenges on income inequality - Ionuț Jianu; Maria-Daniela Tudorache; Andreea Florentina Nicolescu (Proceedings of the 18th International Conference on Business Excellence 2024: Smart solutions for a sustainable future, 21 - 23 March 2024, 2024)
This paper examines the impact of education and labour market challenges on the income inequality in European Union (27 Member States) within the period 2012-2022, this being calculated using the Panel EGLS method. Even if the effects are clearly visible from a theoretical point of view, in the latest years there were not many authors focusing their studies on the effects of the unemployment and early drop-out from school and training on income inequality. In this regard, updating the figures, the impact coefficients and the theoretical background increase the understanding of the statistical processes and their results in the new economic context. Our results confirmed a positive relationship between unemployment rate and income inequality (measured by Gini coefficient), this being also the highest impact found, but also a positive link between the early leavers from education and training rate and income inequality. In addition, we used additional variables to catch the current economic challenges that are related to demographic changes and high energy prices. In this context, we found positive effects exerted by housing cost overburden rate and old-age dependency ratio on income inequality. Even if the model is limited to four income inequality drivers, we have demonstrated that the calculated coefficients are the best linear unbiased estimators.
Keywords: D63; I24; E24; C33; 330; unemployment; education; income inequality; labour market; early leavers; Panel